The time domain for brown dwarfs and directly imaged giant exoplanets: the power of variability monitoring. Issue 1 (2nd January 2017) - Biller, Beth
Abstract: Variability has now been robustly observed in a range of L and T type field brown dwarfs, primarily at near-IR and mid-IR wavelengths. The probable cause of this variability is surface inhomogeneities in the clouds of these objects (although other mechanisms may also contribute), causing a semi-periodic variability signal when combined with the rotational modulation from 3 to 20 h period expected for these objects. Variability at similar or even higher amplitudes has recently been observed in young brown dwarfs and planetary mass objects, which share similar as field brown dwarfs, but have considerably lower surface gravities. Variability studies of these objects relative to old field objects is then a direct probe of the effects of surface gravity on atmospheric structure.